Public Corporation Monopolies - Case Study of Sale of Electricity Company of Ghana (ECG) - Sakyi, Kwesi Atta (Advances in Social Sciences Research Journal, 2019)
This essay begins by examining the theoretical economic underpinnings of different market structures, particularly state monopolies in the form of public utilities in general. The essay examines the case of the sale of the Electricity Company of Ghana (ECG) and analyses why it is being privatised. The essay examines evidence globally and holistically with review of the case for privatisation of the Electricity Company of Ghana, making suggestions for and against privatisation. The insight gained from the essay can inform other African countries (such as Zambia) which are contemplating the sale of their public utilities. The main arguments used for maintaining state monopolies is that they create massive jobs for the people and help the poor access public services cheaply, thereby narrowing the income gap. On the other hand, the main arguments against the continued maintenance of state enterprises is that they are inefficiently run, and they account for the bulk of external public debt of poor countries. Besides, they have been held to ransom by a few politicians and their cohorts whereby these state enterprises are used as conduit pipes for siphoning state funds into the pockets of a few people in privileged political positions. Some of these state monopolies harbour political cadres, failed politicians, and ghost workers. The Washington Consensus and the Bretton Woods institutions which are some of the credible creditors to many African countries have over the years called upon many heavily- indebted African countries to reform and align their loss-making institutions, hence the sale of many of the public institutions such as the Electricity Company of Ghana(ECG). To many an unlettered African, the sale of public utilities is seen as an act of abomination, an unpatriotic act, and a politically-motivated move. It is the objective of this essay to debunk these faulty theses or premises and lay bare the facts. Key words: public utility, state-owned enterprise, public corporation, energy, electricity, privatisation, denationalisation, rationalisation, efficiency, state monopoly. ECG, market structures, divestiture